Difference in marginal bone loss around implants between short implant-supported partial fixed prostheses with and without cantilever: a retrospective clinical study - Josef Al-Kilani; Sedef Al-Kilani; Bruno Ramos Chrcanovic (SpringerOpen, 2023)
Abstract Purpose To investigate the influence of cantilever prosthetic arm on the marginal bone loss (MBL) over time around dental implants supporting short fixed partial dentures (FPDs), in a record-based retrospective study. Methods All cases of 3-unit implant-supported FPDs, supported by 2-3 implants, from the database of cases treated at one specialist clinic were considered for inclusion. Only implants with a minimum of 36 months of radiological follow-up were considered. Univariate linear regression models were used to compare MBL over time between 12 clinical covariates, after which a linear mixed-effects model was built. Results One-hundred-thirty-nine patients (64 men, 75 women) with 164 3-unit implant-supported FPDs (333 implants supporting non-cantilevered FPDs, 94 supporting cantilevered FPDs) were included in the study. The patients were followed up clinically and radiographically for a mean of 154.1 ± 78.0 (min-max, 37.3-364.6) and 132.9 ± 77.3 months (min-max, 36.8-329.9), respectively. The total number of marginal bone level double measurements (mesial and distal sides of each implant) was 2909. FPDs with cantilever presented an estimated greater MBL over time compared to FPDs without cantilever. Bruxism, sex (women), implant (modified) surface, and (poor) bone quality were also associated with higher MBL over time. Conclusions The use of a cantilever extension is suggested to negatively affect the bone marginal level over time around implants supporting 3-unit FPDs. Due to the small difference of the estimated MBL over long periods of follow-up between the groups, it is a matter of debate if the observed negative effect may be of clinical significance. Graphical Abstract